A Recently Discovered Republican Altar in the Centre of Ostia.: The Excavations of the Ostia-Forum-Project (OFP) 2016–2019 - Gering, Axel; Menge, Sophie; Pedersen, Trine Bak (Römische Mitteilungen, 2022)
In this paper, the altar of a recently discovered sanctuary in the northeast of Ostia’s forum will be discussed. The altar can be characterised as a ‘ground altar’, a rather uncommon type associated with the worship of chthonic deities. Its key features include a platform with a central fire pit, a ramp, a drain, a sewer, and a ‘libation hole’. The paper gives an overview of the Ostia Forum Project’s surveys and excavations in the area, focusing on the building phases of the altar. It also provides insight into the stratigraphical development and the corresponding dating evidence. Preliminary results on the faunal remains are also included. Thereby are illustrated the functionality of the altar and the associated rituals. The altar is put into a broader context in relation to the sanctuary’s dimensions and thus, to the city’s grid-layout. The altar’s position in the centre of the precinct’s earliest layout might associate it with the foundation of the sacred area and possibly of the castrum of Rome’s first colony itself.